EQ-3 Castration as a Treatment for Seminoma Intratubular Case in Horse - Budhy Jasa Widyananta; Fitri Dewi Fathiyah; Wiwid Rhuwaida (Hemera Zoa, 2018)
Quality Stallions are one of the most expensive aset in the horse farm. Testicular swelling quite common found without specific diagnosis due to lack of experience. Varied supportive diagnosis is needed to confirm the cause. A thirteen years old horse crossbreed stallion had a history of progressive testicular enlargement.